Analisa Pengaruh Perubahan Tata Guna Lahan Terhadap Sistem Drainase Kawasan Jalan Dorak Kota Selat Panjang Menggunakan Program Bantu EPA SWMM 5.0 - Khoirul Ghofirin; Imam Suprayogi; Bambang Sujatmoko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Dorak street in Selat Panjang city an area that in the future is planned as a regional center of government, office and industrial. It is written in the Detailed Spatial Plan (RDTR) Selat Panjang city in 2013-2032.the condition of this area is still dominated by vegetation to absorb the rain now, but with the urban development plan, the vegetation region turned into housing, offices and trade. Such changes affect the condition of the drainage system on the road Dorak so flooding. To prevent more floods it was necessary to predict how much the flod’s high that occurred based on land use in 2032. This study uses EPA SWMM 5.0 to evaluate the ecurade problems. Based on the simulation results with the land usement in 2013 the occurred flood’s high was 0,416 m and the 2032 land usement and flood elevation of 1,165 m. With the change of land use in 2032 floods occur quite high. Gets approximate results with the recent flooding, flood prevention needs to be done by changing the dimensions of the channel. from the simulation results shown channel dimensions are able to cope with the flood is 2.5 m x 2.2 m by adding floodgates.Keywords: Flood, Drainage, EPA SWMM 5.0